Adaptasi Museum Konvensional dalam Upaya Peremajaan Pasca Pandemi Covid - Nastiti, Ratna Andriani; Krisnawatie, Aloysia; Yuanditasari, Aldila (Program Studi Desain Interior Unikom, 2023)
The museum is a building that accommodates visitors to exchange knowledge, education, arts and culture. Along with the development of knowledge and technology, museums in Indonesia are trying to adapt more efficiently and increase engagement with visitors. Some forms of museum adaptation are by creating methods that involve technology to make the visitor experience more interactive. Given the unprecedented pandemic, conventional museums must adapt quickly to create solutions that will have an impact on how museums will be created and designed post-pandemic. As one example, the Covid-19 pandemic has formed new habits in society, such as the call to diligently wash hands and social distancing. The purpose of this research is to find out the adaptation efforts of conventional museum interiors in Java in dealing with pandemics and post-pandemic. The method used in this research is a case study with a descriptive qualitative approach. Several museums in Java Island were selected as museum case studies and discussed regarding the implementation of diffusion theory in the interior of the museum. The result of this research is the formulation of the adaptation of museum interiors on the island of Java in dealing with pandemics and post-pandemic. The formulation is expected to increase knowledge and become a reference for interior designers in efforts to rejuvenating conventional museum interiors.